Treatment with Autologous Adipose-derived Regenerative Cells for Peyronie’s Disease in Men: The Straight @head Pilot Study - Majken H. Wiborg; Rasmus Krøijer; Birgitte S. Laursen; Wahida Chakari; Charlotte Harken Jensen; Jens Ahm Sørensen; Lars Lund (European Urology Open Science)
Background and objective: We evaluated the effectiveness of injecting autologous adipose-derived regenerative cells (ADRCs) into plaque in men with chronic Peyronie’s disease (PD). Methods: This pilot safety study recruited 22 Danish men with chronic PD from an outpatient clinic. Patients received one bolus of ADRCs injected into plaque, with follow-ups at 1, 3, 6, and 12 mo. The primary endpoint was a reduction in penile curvature. Secondary endpoints were serious adverse events in relation to treatment, and patient-reported results for improvements, distress, and unhappiness related to PD. Key findings and limitations: There was no significant difference in curvature after treatment. However, the participants reported subjective improvements, less distress, and a decrease in unhappiness. No severe adverse events were observed during 12-mo follow-up. Conclusions and clinical implications: Injections of ADRCs into PD plaque appear to be safe but had no significant measurable effect on penile curvature. Half of the participants reported a subjective improvement. Patient summary: We studied the safety and effectiveness of injections of patient-derived regenerative cells for chronic Peyronie’s disease. While the curvature of the penis did not significantly improve, the treatment was safe and some men reported a decrease in their distress and an improvement in penile shape.